Pendampingan Optimalisasi Pencatatan Data Daily worker Berbasis Microsoft Excel pada Departemen Human Resources Hotel APendampingan Optimalisasi Pencatatan Data Daily worker Berbasis Microsoft Excel pada Departemen Human Resources Hotel A - Vivin Alifianti Rusyana; Koernia Purwihartuti; Dewi Sekar Ayu (PDPI, 2026)
The hospitality industry requires an orderly workforce administration system, particularly in managing daily workers who support daily operational needs. In the human resources Department of Hotel A in Bandung, daily worker data recording was initially conducted using physical forms before being recapitulated into a digital file. This condition made the data less structured, increased the possibility of misplaced documents, and made it difficult to monitor the number of workers by department. This community service activity aimed to optimize daily worker data recording through assistance in developing and implementing a Microsoft Excel-based template. The implementation method consisted of partner needs identification, workflow mapping, template development, template implementation, and evaluation of the application results. The results show that the Excel template helped organize daily worker data more systematically based on department, section, working date, payment method, and worker category, namely approval and additional. The implementation also improved data accessibility through a shared folder, supported weekly recapitulation, and reduced dependence on physical documents. This activity indicates that simple digitalization using Microsoft Excel can serve as a practical solution for improving human resources administration efficiency in the hospitality industry.